2007
DOI: 10.1192/apt.bp.106.003202
|View full text |Cite
|
Sign up to set email alerts
|

Why don't patients attend their appointments? Maintaining engagement with psychiatric services

Abstract: Patients miss about 20% of scheduled appointments for mental health treatment, almost twice the rate in other medical specialties. Up to 50% of patients who miss appointments drop out of scheduled care. Many who miss appointments because of slips and lapses later rearrange their appointments without adverse consequences. Those that do not are at risk of further deterioration, relapse and hospital readmission. Predictors of non-attendance are complex and linked with the predictors of missed medication. Service … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
267
2
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 250 publications
(289 citation statements)
references
References 85 publications
14
267
2
6
Order By: Relevance
“…Studies also frequently did not clearly operationalize their attendance terms (Operationalized dropout/attendance terms in Table 2), making it difficult first for readers to understand exactly what is being measured, and second, for researchers to replicate the research design. As has been discussed before (Doyle et al, 2014;Mitchell & Selmes, 2007;Nose et al, 2003;O'Brien et al, 2009), this issue runs rampant in the attendance literature, and presents a barrier to furthering this research in a replicable, robust manner.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Studies also frequently did not clearly operationalize their attendance terms (Operationalized dropout/attendance terms in Table 2), making it difficult first for readers to understand exactly what is being measured, and second, for researchers to replicate the research design. As has been discussed before (Doyle et al, 2014;Mitchell & Selmes, 2007;Nose et al, 2003;O'Brien et al, 2009), this issue runs rampant in the attendance literature, and presents a barrier to furthering this research in a replicable, robust manner.…”
Section: Discussionmentioning
confidence: 95%
“…Their review found 23 different predictors to be associated (in at least four studies) with adherence. Mitchell and Selmes (Mitchell & Selmes, 2007) also speak to this conundrum. In their review of attendance in psychiatry, they highlighted several additional areas which can impact engagement, including perceived benefits of care, perceived costs of care, barriers to care, doctor-patient factors, illness factors, and cues to act.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…A great deal of attention has focused on methods to persuade patients to adhere to treatment decisions, without sufficient acknowledgement that avoidance of sometimes complex, costly, and unpleasant regimens may be entirely rational (Mitchell, 2007). By providing a more holistic picture – mapping a range of practices psychiatrists use to initiate decisions in naturally occurring consultations – support for this perspective is offered here.…”
Section: Discussionmentioning
confidence: 99%
“…They may distrust people when they are experiencing paranoia, experience attention deficits (Hamann et al, 2006) or have poor awareness of their illness leading to resistance of medication. Psychiatrists may then use methods to persuade patients to adhere to their treatment (Mitchell & Selmes, 2007). …”
mentioning
confidence: 99%